2020
DOI: 10.2196/14951
|View full text |Cite
|
Sign up to set email alerts
|

Sedentary Work in Desk-Dominated Environments: A Data-Driven Intervention Using Intervention Mapping

Abstract: Background Since desk-dominated work environments facilitate sedentary behavior, office workers sit for 66% of their working days and only 8% succeed in interrupting their prolonged periods of sitting within the first 55 minutes. Yet stretches of long and uninterrupted sitting increase the likelihood of several chronic metabolic and cardiovascular diseases. Objective We therefore developed a computer-based app designed to interrupt periods of prolonged … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(30 citation statements)
references
References 63 publications
1
25
0
Order By: Relevance
“…The process evaluation should be reported to provide important information about how to replicate the intervention and what generalisable knowledge can be drawn from the implementation [ 26 , 27 ]. Encouragingly, there have been several recent sit less studies published which have reported intervention development or implementation processes [ 54 , 55 , 56 , 57 ]. Finally, future research could consider contextual factors that may present as competing priorities and could consider focusing on how to alter organisational culture by challenging the social norms of workplace sitting in order to successfully implement such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…The process evaluation should be reported to provide important information about how to replicate the intervention and what generalisable knowledge can be drawn from the implementation [ 26 , 27 ]. Encouragingly, there have been several recent sit less studies published which have reported intervention development or implementation processes [ 54 , 55 , 56 , 57 ]. Finally, future research could consider contextual factors that may present as competing priorities and could consider focusing on how to alter organisational culture by challenging the social norms of workplace sitting in order to successfully implement such interventions.…”
Section: Discussionmentioning
confidence: 99%
“…nl/ trial/ 7503). The intervention protocol can be found in [27]. The cleaned raw data and additional material are fully disclosed in the supplementary materials (https:// osf.…”
Section: Methodsmentioning
confidence: 99%
“…The development of UPcomplish using evidence from the literature and from theories (e.g. reasoned action approach [33]) is described elsewhere [27]. Shortly, the problem of SB was refined, and behavioural outcomes, and performance objectives (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moderators of the effectiveness of UPcomplish on sedentary behavior, quality of life, and psychosocial determinants: A stepped-wedge design Berninger, N. M., Crutzen, R., Ruiter, R. A. C., Kok, G., Plasqui, G., & ten Hoor, G. A. (2020).…”
Section: Chaptermentioning
confidence: 99%